2021
DOI: 10.3390/nursrep11010011
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Computers: The Hidden Work of Clinical Nurses during the Introduction of Health Information Systems in a Teaching Hospital in Taiwan

Abstract: Implementing health information systems for enhancing patient care and management occurs worldwide. Discovering how nurses, as important system end-users, experience technology-reliant clinical practice involved focus groups (n = 25) and in-depth individual interviews with nurses (n = 4) and informatics staff (n = 3) in a major Taiwanese medical center. This qualitative study explores the unintended effects of these systems on nurses’ role and clinical practice. First, nurses’ additional role caring for comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The study demonstrated positive perceptions of the usefulness of health information technologies, with high levels of agreement for the use of health information technologies for patient administration (88.2%), analysis and planning patient care (81.7%) and communication with patients (78.5%). This is consistent with a study reporting that nurses perceived the use of health information systems for patients' data collection and documentation, allowing nurses to spend more time on patient care while improving accessibility and efficient documentation (Huang 2021). This finding, however, was also in contrast (again) with the reported low level of ability of the respondents to use health information technologies for patient administration and management.…”
Section: Perceived Ease Of Use and Perceived Usefulness Of Health Inf...supporting
confidence: 88%
“…The study demonstrated positive perceptions of the usefulness of health information technologies, with high levels of agreement for the use of health information technologies for patient administration (88.2%), analysis and planning patient care (81.7%) and communication with patients (78.5%). This is consistent with a study reporting that nurses perceived the use of health information systems for patients' data collection and documentation, allowing nurses to spend more time on patient care while improving accessibility and efficient documentation (Huang 2021). This finding, however, was also in contrast (again) with the reported low level of ability of the respondents to use health information technologies for patient administration and management.…”
Section: Perceived Ease Of Use and Perceived Usefulness Of Health Inf...supporting
confidence: 88%
“…18 The development of information technology in the field of nursing indicates that nursing science technology is trying to keep pace with the dynamic development of IT. 19 This article attempts to analyze the perception of nurses' readiness in Indonesia regarding the use of IT in dealing with the new variant of Omicron. The objective is to measure the nurses' readiness that needs emphasizing and improvement so that they can be used as materials to improve the nursing services during COVID-19 pandemics.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the provision of education. The role of IT in nursing education is so important 19 , from teaching materials, delivery of teaching materials, references, research tools and equipment, learning evaluation systems and other aspects of the teaching and learning process all require IT support. 19,37 In the era of globalization, nursing students' learning emphasis on IT competencies is everyone's need.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation